Anion–pyridine-n-oxime interplay to control metal–metal separations in a series of Cu(ii) coordination polymers. Issue 35 (3rd September 2022) - Croitor, Lilia; Coropceanu, Eduard B.; Fonari, Marina S.
Abstract : The possibility to tune the metal–metal separations in a series of ten Cu(ii ) 1D and 2D coordination polymers obtained from pyridine- n -oxime–dicarboxylic acid blends was followed and discussed. Abstract : Ten mixed-ligand one-(1D) and two-dimensional (2D) Cu(ii ) coordination polymers that include: [Cu(SiF6 )(4-pyaoH)4 ]·dmf·0.5H2 O n (1 ), [Cu(mal)(4-pyaoH)2 ]·dmf n (2 ), [Cu(mal)2 ](4-pyaoH2 )2 n (3 ), [Cu(adi)(3-pyaoH)2 (H2 O)] n (4 ), [Cu(adi)(3-pyaoH)2 ] n (5 ), [Cu(adi)(3-pyaoH)2 ]·0.6MeOH·0.3H2 O n (6 ), [Cu(seb)(3-pyaoH)2 ]·H2 seb·H2 O n (7 ), [Cu(ClO4 )(2-pyao)(2-pyaoH)] n (8 ), [Cu(oxa)(2-pyaoH)]·H2 O n (9 ) and [Cu3 (μ3 -OH)(2-pyao)3 (fum)]·6.5H2 O n (10 ) were obtained by reactions of Cu(ii ) salts with binary blends of isomeric pyridine- n -oximes ( n -pyaoH, n = 2–4) and dicarboxylic acids (oxalic = H2 oxa, malonic = H2 mal, fumaric = H2 fum, succinic = H2 suc, adipic = H2 adi, and sebacic = H2 seb). Compounds 1–4, and 8, 9 represent chain-type coordination polymers with the single Cu(ii ) atom as a metal building block bridged by the inorganic or organic anions while the pyridine- n -oxime ligands occupy the terminal positions and coordinate in the monodentate or bidentate–chelate coordination mode. The extension of structures up to 2D coordination networks in 5–7 is derived from the bidentate-bridging function of the neutral 3-pyaoH ligand acting through the N -pyridine and O -hydroxyl binding sites. A linear coordination polymer 10 is unique in this series bearing trinuclear [Cu3 (μ3 -OH)(2-pyao)3 ] 2+ metallacrown cores bridged by fumarato linkers. The possibility to tune the Cu(ii )⋯Cu(ii ) separations in the reported 1D and 2D coordination polymers through coordination and intermolecular H-bonds was demonstrated and discussed.